Global stability of fractional feedback nonlinear systems with interval matrices of positive linear parts and application to electrical circuits - Kaczorek, Tadeusz (1932- ) (Zielona Góra: Uniwersytet Zielonogórski)
The global stability of fractional multi-inputs multi-outputs continuous-time nonlinear feedback systems with interval matrices of positive linear parts and application to electrical circuits is investigated. New sufficient conditions for the global stability of fractional nonlinear systems are given. The new stability conditions are applied to nonlinear electrical circuits and demonstrated on a simple example of a fractional nonlinear feedback system with a positive linear part.
Keywords: global stability; fractional order; positive nonlinear system; electrical circuit